THE EFFECT OF AN EDUCATIONAL CURRICULUM USING THE BARNES MODEL ON DEVELOPING CREATIVE THINKING AND LEARNING SOME OFFENSIVE HANDBALL SKILLS FOR SECOND-STAGE STUDENTS AT THE UNIVERSITY OF THI-QA - Majid Mohammed Msaed; Farazdaq A. Hmddan; Abrar Jabbar Ammar Al-Jaberi (Galaxy International Interdisciplinary Research Journal, 2024)
The study sought to determine the impact of Barnes’ paradigm on enhancing creative thinking in the acquisition of offensive skills. Hence, the significance of research is demonstrated through the application of the Barnes educational model and its influence on fostering creative thinking and acquiring fundamental handball skills. This model facilitates the assessment of student learning in a precise scientific manner, highlighting the inadequacy of contemporary strategies and models in skill acquisition. Consequently, researchers have recognized the value of implementing the Barnes educational model to enhance creative thinking among students. Therefore, one of the research objectives is to determine the influence of the Barnes model on the enhancement of creative thinking skills, specifically in relation to learning handball. The researchers employed an experimental approach, utilizing a pre-and post-test design with both experimental and control groups. The study was conducted within the student population of the second stage in the College of Physical Education and Sports Sciences at the University of Thi-Qar during the academic year (2022/2022), with a total of 152 participants. The researchers concluded that incorporating the Barnes method in educational units enhances learners’ skill performance in offensive skills. Additionally, this method boosts students’ motivation and enthusiasm while directing their attention toward improving motor performance. The primary suggestions were to implement the utilization of educational modules developed by researchers, following the Barnes method, after their efficacy was demonstrated on second-stage students at the Faculty of Physical Education and Sports Sciences - University of Thi-Qar. The focus was on applying this educational approach to acquire offensive skills in different games, due to its beneficial influence on enhancing the learning process.